MEDIAÇÃO CULTURAL E SOCIALIZAÇÃO NO PROCESSO DE AQUISIÇÃO/APRENDIZAGEM DE LÍNGUA ESTRANGEIRA - Bullio, Paula Cristina (Línguas & Letras, 2000)
Nowadays there is the necessity to learn another language to achieve: education, better job and standard of living. However, the process of acquisition is complex, mainly because we have to consider the relation of language and culture and also the importance of learning rules and social roles in specific contexts.